Development of Interactive Map Media for Teaching the Distribution of Indonesian Flora and Fauna in Senior High School Geography - Narasrestha, Ni Kadek Indrena Gupta; Sriartha, I Putu; Dwipayana, Made (CV. Tripe Konsultan, 2025)
Geography learning requires appropriate media to concretize abstract concepts, such as the distribution of flora and fauna in Indonesia, which varies significantly across the archipelago. Conventional maps commonly used in schools often lack the flexibility and interactivity needed to present geospatial information effectively and dynamically. Therefore, this study aims to develop an interactive map-based learning media to enhance students’ understanding of the distribution of Indonesian flora and fauna in Senior High School geography subjects. The study applies a Research and Development (R&D) method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The interactive map was designed using base maps derived from thematic data, combined with digital or satellite imagery, to produce a more comprehensive and engaging geospatial visualization. Features of the media include layers of flora and fauna distribution, geographic characteristics, interactive videos, quizzes, learning materials, and lesson plans. The media is also supported by clear icons, appropriate cartographic symbols, and color gradations based on cartographic principles to improve readability and spatial interpretation. The developed media was tested on students at SMAN 1 Penebel, Tabanan Regency, Bali. Validation results from content, language, and media experts indicated a very high level of validity. In addition, practicality assessments by teachers and students showed that the media is easy to use and effective in classroom settings. Pre-test and post-test comparisons revealed a significant improvement in student learning outcomes, with an average post-test score increase of 28.75 points. These results suggest that interactive map media can significantly enhance the effectiveness of geography learning.